EXPLORANDO O DESCONHECIDO: INFLUÊNCIAS PALEOGEOGRÁFICAS NA DISTRIBUIÇÃO DOS PEIXES DE ÁGUA DOCE DO MARANHÃO - ABREU, João Marcelo da Silva (2020)
South America, and especially the Amazon basin, has been the subject of a large amount of studies on its paleogeographic and paleoenvironmental history, in order to understand the historical conditions that gave rise to one of the highest concentrations of biodiversity on the planet. However, studies like these are poorly developed in the coastal regions of northeastern Brazil. Thus, this study aimed to identify the main biogeographic events responsible for the distribution of freshwater fish in the hydrographic basins of Maranhão, a little-known area of the Neotropical realm, and explain their actions in the dispersal, extinction and speciation of these species in this region. Marine incursion and regression events are known to greatly influence the landscape design of the Brazilian coastal region, so we sought to identify the degree of influence of these events to the target region of the study and to compare their effects on adjacent basins. The survey of freshwater fish species listed for maranhenses drainages was carried out to evaluate species richness and composition through paleogeographic and community phylogenetic methods. Genetic analyzes were also used in two species of the region, seeking to evaluate the existence of differentiation between populations of different basins and which events were responsible for this process. Finally, we review the geomorphological data published so far, which may have contributed to the process of distribution of freshwater fish in Maranhão and the consequent process of differentiation of their species. Thus, we identified that the Maranhão basins, in the same way as the Amazon basin, were strongly influenced by sea level variation events, a factor that is mainly due to the composition of the area through low altitude plains. We present the most extensive taxonomic list so far for the Maranhão basins, with a total of 160 species and identified that the Mearim and Itapecuru basins were occupied about 9 Ma, serving as a source for the formation of the assemblies of the other basins. Through the genetic analyzes employed, we identified that populations from the Turiaçu basin are differentiating themselves from the others, while populations from the other basins still present a close genetic proximity. Based on these results, we found that the composition and distribution of freshwater fishes in the Maranhão river basins was mainly influenced by the events of marine transgressions and regressions, as well as the formation of paleodrainage, activation and reactivation of faults, arches and lineaments, the Serra do Tiracambu uplift and by river capture events. Moreover, we can infer that the dispersal, differentiation and extinction processes are still underway, demonstrating the importance of understanding these biogeographic events together with the studies of species biology and ecology, for the elucidation of their evolutionary histories.